The Gold Crusades : a Social History of Gold Rushes, 1849-1929. - Fetherling, Douglas (Heritage., 1997)
Fetherling argues that the gold rushes in the US, Canada, Australia, New Zealand, and South Africa shared the same causes and results, the same characters and characteristics.